Dining in the lions den Bel and the dragon, verses 2842 (Old Greek/Theodotion) - Joseph J. de Bruyn (Verbum et Ecclesia, 2015)
This article is part of a series of articles written on Bel and the dragon. This series of articles is an investigation into the Greek editor/authors use of body, space, narrative and genre in creating a new reality regarding the Jewish deity. A spatial framework is used to specifically examine the third episode of Bel and the dragon, entitled Dining in the lions den. It is suggested that the third episode of Bel and the dragon should be read in a reciprocal relationship with not only Bel and the dragon but also the larger book of Daniel. Firstly, such an analysis indicates that the smaller episode is part of a larger clash of deities. Secondly, it shows that the editor/ author utilises the episode to recreate a new cosmology. In this new cosmology, the God of Israel is an almighty deity whilst other deities are revealed as false and not real living gods. In his own way, the editor/author contributes to the way in which Jews regarded their God within the reality of the diaspora. Intradisciplinary and/or interdisciplinary implications: The aim with this article was to analyse Daniel 14 by means of new insights from developments in language studies. Until now, scholars tended to repeat each other in their analysis of Daniel 14. No attention was given to space, body or other aspects of new developments in the field of language. This article challenges the repetitive research previously done on Daniel 14.